THE ANALYSIS OF THE MAIN CHARACTER'S QUARTER-LIFE CRISIS FROM THE MOVIE "SOUL" BY PETE DOCTER - Rianna Jona Sumampouw (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The Analysis of the Main Character’s Quarter-Life Crisis from the Movie “Soul” by Pete Docter Rianna Jona Sumampouw Elisabet Natalia Umbas Abstract The presence of the film "Soul" by Pete Docter has been momentous for the portrayal of the quarter life crisis. Disney Pixar definitely had an impact on the perceptions of those who had gone through that phase. The purpose of this study is to dig deeper into how we can understand what Pete Docter wants to convey a message of not only achieving one’s dream but also feeling you lost a part of yourself. Besides that, it also demonstrates how humans tend to forget the good people that helped them achieved their dream resulting them in being selfish and visualizes an interesting way of quarter life crisis that could clear up some doubts of the afterlife. It will shed light on the science and reasons behind such influence in their personal lives and determine how they view the characters who are facing a quarter life crisis. In turn, conceptualizing the level of care in understanding characters will help gain a better understanding of how the film industry can work and the role it plays in sending messages to its audiences is beneficial. In doing this research, the researcher used qualitative method and collected the data by watching the movie “Soul” to analyze the main character’s quarter-life crisis. Some of the data has been taken from internet and books. Based on the analysis in the previous chapter, the researcher would like to conclude on how to solve the quarter life crisis from the hit Pixar movie “Soul” by Pete Docter. The exploration and development of Joe's character did not feel forced because Joe is portrayed as an ordinary man who is learning to live, the audience can most definitely relate to this experience. The story that focuses on Joe’s character who is depicted as flat has an interesting balance as the character named 22 adds a bit of flavor to the storyline, giving it a contradictory flavor. The characters Joe Gardner and 22 offer important advice to those who are still confused on their purpose of life. In addition, the director and scriptwriter Peter Docter seemed to want to invite the audience to participate in questioning the purpose of life through scene by scene. It may seem simple, but it's actually very meaningful